An effort to find new α-amylase inhibitors as potent antidiabetics compounds based on indole-based-thiadiazole analogs. Issue 23 (19th December 2022) - Taha, Muhammad; Uddin, Nizam; Saad, Syed Muhammad; Iqbal, Naveed; Fareed, Ghulam; Anouar, El Hassane; Hassan, Maya Haj; Almandil, Noor Barak; Salahuddin, Mohammed; Khan, Khalid Mohammed; Wadood, Abdul; Rahman, Ashfaq Ur
Abstract: Inhibition of α-amylase enzyme is of key significance for the therapy of diabetes mellitus (DM). Numerous indole-based compounds have earlier been described for broad range of bioactivities. From our previous study, we knew that indole and thiadiazole are potent inhibitors of diabetics II. We design the hybrid molecules of them and synthesized 18 derivatives of indole-based-thiadiazole (1 –18 ). All synthesized compounds were characterized using different spectroscopic methods and evaluated for their α-amylase inhibitory activities. All synthetic compounds, except 4, 13, 15 and 16, were found to be strongly active (IC50 values in the range of 0.80 ± 0.05 − 9.30 ± 0.20 µM) than the standard drug, acarbose (IC50 = 11.70 ± 0.10 µM). Nevertheless, compound 18 was found to be inactive. The modes of binding interactions of five most active compounds 2, 3, 5, 10 and 17 were also studies through molecular docking study. In brief, current study identifies a novel class of α-amylase inhibitors which can be further studied for the treatment of hyperglycemia and obesity. Communicated by Ramaswamy H. Sarma